The Living Qur’an: Its Text and Practice in the Function of the Scripture - Rafiq, Ahmad (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2021)
Since firstly appeared in an informal conversation among the faculty members at the Qurʾanic and hadith studies program at the Faculty of Ushuluddin, Religious Studies, and Islamic Thought of IAIN Sunan Kalijaga Yogyakarta in 2005, scholars have ventured to develop the concept of Living Qurʾan, pursuing to determine it’s proper or best formats, scopes, methods, and approaches. It is my contention that Living Qurʾān is yet to find its epistemological and methodological infrastructures. It is in this context this paper aims to contribute. It firstly offers my construction of the term along with its conceptual consequence. Then, I propose the mapping of the relationship between scripture and its community, built on the relational concept of scripture. Finally, this article elaborates on the transmission and transformation patterns through which knowledge, practices, and discourse forming the Qurʾānic reception between its community. It is hoped that with these three subjects, this paper would emulate further discussion about Living Qurʾan at the epistemological and methodological level.